Parametric optimization of Cu (II) and Ni (II) adsorption onto coal dust and magnetized sawdust using box-behnken design of experiments - Kapur M.; Gupta R.; Mondal M.K. (My University, 2025)
The simultaneous removal of Cu (II) and Ni (II) ions from aqueous solution was investigated by using two different adsorbents (coal dust and magnetized sawdust). Experiments were made as a function of initial metal concentration (5–100 mg/L), adsorbent dose (2–20 g/L), and temperature (20–40°C) for the adsorption of metals by employing response surface methodology (RSM) based on Box–Behnken surface statistical design. The pH was kept constant at 4 and 5 for coal dust and magnetized sawdust, respectively. The magnetized sawdust showed better results for both Cu (II) and Ni (II) removal as compared with coal dust. The F statistics and ANOVA analysis confirmed that the model chosen to explain the relationship between the factors and the response is correct. For this work, three-level three-factorial experimental design has been applied to validate adsorption parameters affecting the combined removal of Cu (II) and Ni (II) onto coal dust and magnetized saw dust. Optimization of process parameters for Cu (II) and Ni (II) ions adsorption onto the adsorbents was done using RSM. The empirical relationship between the response (adsorption percentage of heavy metal) and the independent variables (initial heavy metal concentration, adsorbent dose, and temperature) has been expressed by the quadratic models. These models in turn help to understand and establish the optimized set of conditions without performing the unnecessary experiments at various combinations. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1597–1604, 2016. © 2016 American Institute of Chemical Engineers Environ Prog